1985
DOI: 10.1111/j.1502-3931.1985.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Bryozoans as substratum of fossil fistulose Foraminifera (Fam. Polymorphinidae)

Abstract: Ehrhard 198504 15: Bryozoans as substratum of fossil fistulose Foraminifera (Fam. Polymorphinidae). Lethaia, Vol. 18, pp. 155-165. Oslo. ISSN 0024-1164.In the Upper Cretaceous-Lower Tertiary sections exposed in the Curfs quarries at Berg (munic. Berg en Terblijtalso known as Geulhem, southern Netherlands) and some other localities, numerous foraminifers of the family Polymorphinidae with complete fistulose apertures have been found. These apertures, which are equipped with circular openings and auxiliary apert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Through attachment of foraminifers to dead bryozoans, the foraminiferans benefited from the provision of a sheltered substrate in high‐energy environments (cf. Pożaryska and Voigt, ).…”
Section: Biofaciesmentioning
confidence: 99%
“…Through attachment of foraminifers to dead bryozoans, the foraminiferans benefited from the provision of a sheltered substrate in high‐energy environments (cf. Pożaryska and Voigt, ).…”
Section: Biofaciesmentioning
confidence: 99%
“…According to Thomsen (1977), encrusting bryozoans from Danian mounds in Denmark preferred to attach to erect bryozoans with smooth rather than ridged surfaces. Pozaryska and Voigt (1985) made a detailed study of fistulose foraminiferans attached to erect and vagile bryozoans of Upper Cretaceous and Palaeocene age. They concluded that attachment could occur to both dead and living bryozoans, the foraminiferans benefiting from the provision of a sheltered substrate in high-energy environments.…”
Section: Bryozoan-hosted Skeletobiontsmentioning
confidence: 99%
“…Alternatively, the foraminifers may have lived interstitially on stable clasts below the sediment-water interface, although this idea is not supported by the fact that in examples where the way-up when collected is known, in six cases the foraminifer was only on the upper side of the clast and in no cases was it found only on the underside. There is no morphological Pozaryska and Voigt (1985).…”
Section: Foraminiferamentioning
confidence: 99%